EFFECT OF GENDER ON FARMERS’ OWNERSHIP, CONTROL AND ACCESSIBILITY TO CLIMATE CHANGE ADAPTATION RESOURCES IN SOUTHWEST NIGERIA - Ogunjinmi, kehinde Oluwaseye; Fakoya, Emmanuel Olugbenga; Banmeke, Tajudeen Oyekunle Amoo; Fapojuwo, Oluwakemi Enitan; Ogunjinmi, Anthony Adenkule (FUDMA Journal of Sciences, 2022)
The ability to access, control and own adaptation resources is a critical factor in determining rural farmersâ€™ adaptive potential and decision-making towards adaptation to climate change.  This study investigated the effect of gender on farmersâ€™ accessibility, control and ownership of climate change adaptation resources in Ogun and Ekiti States respectively, Nigeria. Three hundred and fifty eighty men (358) and (222) women farmers were randomly selected through a multi-stage sampling procedure. A pre-tested questionnaire was used to obtain data and analysed with frequency counts, means, percentages, Chi-square.  A positive and statistically significant association (P
Keywords: Access, control, ownership, climate change, capacity